Usability and Privacy Aspects of Moodle: Students’ and Teachers’ Perspective - Ivanović, M.; Putnik, Z.; Komlenov, Ž.; Welzer, T.; Hölbl, M.; Schweighofer, T. (Informatica)
Usability and Privacy Aspects of Moodle: Students' and Teachers' Perspective